Démilitarisation et reconversion de l’héritage militaire - Anne Mathis; Denis Mathis (Projets de Paysage)
Military redeployment within the country has freed up many military infrastructures at the heart of the urban and peri-urban landscapes of garrison towns. The landscape of the garrison district of the town of Metz is the result of successive strata of military installations from different periods. The gradual departure of the Army has led to the transfer and restitution to the town of closed blocks of barracks and fortified enclosures. How does the city of Metz reorganise these demilitarised areas to transform an inherited landscape with a marked identity into a part of its heritage? Functional reconversion is accompanied by a process of “heritagisation” through the rehabilitation of the former barracks of Steinmetz, or in the re-qualification of the site of Mont Saint-Quentin.